Inheritance Rights for Children from Siri Marriage in Indonesia - Ayu Oktavia; Sri Budi Purwaningsih (Indonesian Journal of Law and Economics Review, 2018)
In Indonesian society, there are still many marriages that are not registered officially or commonly called with Siri marriage. Siri marriage is a legitimate marriage according to religion but illegitimate according to the state's rule, which in turn affects the child whose born of Siri marriage. Children born out of Siri marriage cannot get their rights especially in terms of inheritance rights. The purpose of this study is to determine whether or not there is legal protection for children born of Siri marriage in terms of inheritance rights in view of the positive laws prevailing in Indonesia. The research method used is Normative research method using statutory approach (statute approach). In Indonesia related to the protection of inheritance rights for children born of siri marriage there are some differences. The benefit of this research is to increase the knowledge of whether or not there is legal protection in terms of inheritance rights for children born from siri marriage in review of the positive law in Indonesia.